Annexin A3 as a Marker Protein for Microglia in the Central Nervous System of Rats - Zengli Zhang; Zhengyiqi Li; Zhi Ma; Meiling Deng; Manyu Xing; Jing Wu; Shasha Jiang; Qiang Wang; Qulian Guo; Wangyuan Zou (Neural Plasticity)
The parenchymal microglia possess different morphological characteristics in cerebral physiological and pathological conditions; thus, visualizing these cells is useful as a means of further investigating parenchymal microglial function. Annexin A3 (ANXA3) is expressed in microglia, but it is unknown whether it can be used as a marker protein for microglia and its physiological function. Here, we compared the distribution and morphology of parenchymal microglia labeled by ANXA3, cluster of differentiation 11b (CD11b), and ionized calcium-binding adaptor molecule 1 (Iba1) and measured the expression of ANXA3 in nonparenchymal macrophages (meningeal and perivascular macrophages). We also investigated the spatiotemporal expression of ANXA3, CD11b, and Iba1 in vivo and in vitro and the cellular function of ANXA3 in microglia. We demonstrated that ANXA3-positive cells were abundant and evenly distributed throughout the whole brain tissue and spinal cord of adult rats. The morphology and distribution of ANXA3-labeled microglia were quite similar to those labeled by the microglial-specific markers CD11b and Iba1 in the central nervous system (CNS). ANXA3 was expressed in the cytoplasm of microglia, and its expression was significantly increased in activated microglia. ANXA3 was almost undetectable in the nonparenchymal macrophages. Meanwhile, the protein and mRNA expression levels of ANXA3 in different regions of the CNS were different from those of CD11b and Iba1. Moreover, knockdown of ANXA3 inhibited the proliferation and migration of microglia, while overexpression of ANXA3 enhanced these activities. This study confirms that ANXA3 may be a novel marker for parenchymal microglia in the CNS of adult rats and enriches our understanding of ANXA3 from expression patterns to physiological function.